Proarrhythmic effect of radiofrequency catheter ablation on the right ventricular moderator band. Issue 5 (9th July 2022) - John, Roy M.; Willner, Jonathan
Abstract : Following ablation on the RV moderator band for suppression of monomorphic PVCs, recurrent VT and VF were triggered by the same PVC at shorter coupling intervals. This is likely a pro arrhythmic effect of ablation on the moderator band.